Moderní trendy v nosných konstrukcích jeřábů - Hájková, Barbora (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Práce se zabývá zpracováním kritické rešerše problematiky nosných konstrukcí jeřábů se zaměřením na věžové jeřáby. Vysvětluje základní pojmy související s konstrukcí jeřábu a jejích dílů. Cílem práce je kritické zhodnocení trendů do budoucna.

The thesis presents the critical research on the bearing constructions of cranes with a special focus on the tower cranes. It explains the basic terms related to the crane construction and its parts. The aim of this work is a critical evaluation of the future trends.
Modern trends in the supporting structures of cranes
Keywords: Jeřáby; ocelové konstrukce; pruty; styčníky; Cranes; steel constructions; rods; joints